1975
DOI: 10.1007/bf01408150
|View full text |Cite
|
Sign up to set email alerts
|

New levels observed in188Os from the decay of188Re

Abstract: Abstract. The level structure of ~8SOs has been investigated following the decay of 17 h l SSRe. The energies and relative intensities of 41 gamma rays were determined using large volume high resolution Ge(Li)detectors. The decay was observed to populate the 0 + states at 1478 and 1 704 keV which were recently observed in (p, t) reaction studies. Additional states at 1 414 and 1 843 keV were also observed in the decay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1975
1975
1988
1988

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 10 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Casten and Cizewski [1] showed that it is possible to reproduce the B(E2) branching ratios in the frame of the IBA-1 model, while Bijker et al [2] got better agreement for level energies by considering the difference between protons and neutrons explicitely (IBA-2). The very complex level scheme of ~88Os has been studied by the decay of 188T_ 18s]~ o 77~t111 [3] and 75..~113 [4] as well as by various nuclear reactions [5] including partial (n, 7) -works [6][7][8][9]. Further information on this level scheme is given in the present work mainly based on direct and coincidence neutron capture y-ray spectroscopy with Ge(Li)-detectors.…”
Section: Introductionmentioning
confidence: 99%
“…Casten and Cizewski [1] showed that it is possible to reproduce the B(E2) branching ratios in the frame of the IBA-1 model, while Bijker et al [2] got better agreement for level energies by considering the difference between protons and neutrons explicitely (IBA-2). The very complex level scheme of ~88Os has been studied by the decay of 188T_ 18s]~ o 77~t111 [3] and 75..~113 [4] as well as by various nuclear reactions [5] including partial (n, 7) -works [6][7][8][9]. Further information on this level scheme is given in the present work mainly based on direct and coincidence neutron capture y-ray spectroscopy with Ge(Li)-detectors.…”
Section: Introductionmentioning
confidence: 99%